Analysis of the level of productive financing at Bank Syariah Indonesia KCP Gowa - Kadir, Amiruddin; Susono, Juhasdi; Zulkifli, Zulkifli (Journal of Islam and Science, 2023)
Sharia financial institutions are a reflection of the growing desire among individuals for sharia-compliant economic operations. This study aims to find out what factors cause low productive financing at PT. Bank Syariah Indonesia KCP Gowa, the strategy used by PT. BSI in increasing productive financing (mudharabah and musyarakah). The research approach used in this research is descriptive qualitative with data collection methods, namely using observation, interviews and documentation studies. The types of data used in this research are primary data and secondary data. The results of the research show that there have been ups and downs in the growth rate of total productive financing in the last 4 years and there are 5 (five) factors that cause the low level of productive financing (mudharabah and musyarakah), namely crisis of confidence, financing risk, profit sharing, limited to customers who already have business as well as the limited business sectors that are financed and there are several strategies in increasing productive financing (mudharabah and musyarakah) at PT. Bank Syariah Indonesia KCP Gowa, namely education, increasing the capacity of the bank's Micro Head Unit (UHM), collaborating with other partners to provide guidance to debtors, and this guidance must be carried out on an ongoing basis. This is very important for PT. Bank Syariah Indonesia KCP Gowa has the potential to generate profits which will affect the level of profit obtained by the bank.